Método periódico para interpretar propriedades dos materiais - Gurgel, Maria Fernanda do Carmo (2005)
In this work was done mecanic-quantic periodic in level ab initio and using the density functional theory (DFT) combined with the B3LYP (BECKE 1993; LEE, et al 1998) to a series of titanates. Models periodic simulations were used to do a system study about structure property, electronics and optics and analyze the dislocation influence over this materials structure and to study too the doping influence, using the CRYSTAL98 program. With objective of characterize the electronic levels of the BT (titanate barium) materials pure and BT doped with Mn and BST (barium and stroncium titanate). This electronic levels were analyzed from state density projections in the region between upper limits of the valence band and inferior of the conduction band, were analyzed the structure band and electronic densities with objective of comprehend better the photoluminescence properties of this materials in the amorphous phase (desordered structure). To realize the photoluminescence propriety study of materials used date obtained by Rietveld refinement and two periodic models of super cell were developed order structure (phase cristaline) and desordered structure (phase amorphous), in analyze were built three periodic models to theoric BT and of pure refines and of the doped with objective to offer a new alternative of a mecanic-quantic periodic model to simulate the structure deformation induce by Mn doping in the BT. This modelization became possible give general acess of the doping effect in the electronic structure and still to analyzed the doping element influence in the disposition electronic configuration, considering that Mn isn t included in the simulation but this dope effects were noted with the refinement of Rietveld date used. All theoric results obtained were correlation with experimentals results to investigate and interpret better these materials proprieties.